Effect of roflumilast in patients with severe COPD and a history of hospitalisation. Issue 1 (6th July 2017) - Rabe, Klaus F.; Calverley, Peter M.A.; Martinez, Fernando J.; Fabbri, Leonardo M.
Exacerbations of chronic obstructive pulmonary disease (COPD) are acute events characterised by a worsening of respiratory symptoms that necessitates a change in medication and/or hospital admission [1]. Severe exacerbations (those resulting in hospitalisation and/or death) are associated with a poor prognosis [2], decreased quality of life [3] and higher mortality [2, 4]. Roflumilast is a once-daily, oral, selective phosphodiesterase-4 inhibitor that targets both the systemic and pulmonary inflammation associated with COPD [5]. Previous studies have shown that roflumilast as an add-on to inhaled therapies reduces COPD exacerbations in patients with severe COPD who have chronic bronchitis and a history of exacerbations [6–9]. However, the adverse events associated with systemic therapies such as roflumilast necessitate that these therapies are used to treat specific patient populations in whom they are likely to have the greatest clinical benefit [10]. Roflumilast provides greater therapeutic benefit in severe COPD patients with a hospitalisation in the prior year http://ow.ly/lzWy30bNBd4